Performance Analysis of a Sky-Wave Over-the Horizon Radar Simulation Tools - Zenon Saavedra; Adrian Llanes; Gonzalo Alderete Hero; Julian Di Venanzio; Ana Geogina Elias (Revista Elektrón)
This paper presents the main features of a skywave over-the-horizon radar simulation software and results on its ability to represent and detect different search scenarios. Through a series of simulations of the primary phenomena involved in the search process, the software can estimate the behaviour of a radar system in different scenarios. This capability allows the simulator to assist in selecting the most suitable radar configuration to achieve an acceptable level of successful detection probability for a given set of scenarios. It also facilitates various studies and analyses of different factors present in the behaviour of these types of radars.